PERENCANAAN ULANG GEDUNG PENUNJANG MEDIK RUMAH SAKIT BHAYANGKARA SARTIKA ASIH DENGAN KONSEP BANGUNAN HIJAU - Puspitasari, Ira; Rahmatullah, Ridhwan Muhammad Fauzan; Prasetyo, Denny Adi (UPPM Politeknik TEDC Bandung, 2023)
The infrastructure facility makes a major difference in human life. Its progression has definitely been for good and for bad. One of the bad effects is global warming. For repressing the harmful effects requires a new concept that remains environmental. The medical facility support building at the medical center in Bandung is still on its way to implementing the concept of green building. The building is planned to add solar power systems to its energy source. This Solar system is planned to apply on the roof. According to the roof's calculations, the number of solar panels should be installed at 250 units and require 33 units inverter. The installation of this system eventually affected the structure of roof plates. The building's inner design involves a steel framing structure for columns and beams. Reinforced concrete slab roof is used. The structure of the Structure Of Order Bearers Special Moments (SRPMK) referred to the area of the earthquake 4. The earthquake load calculations used an equatorial static that works on the portal passage. Style-counting analyzer in manually counted and of sap2000 version 14.0.0. Portal planning uses Load Resistance Factor Design (LRFD) method to determine the profile used. After calculations were made, it was found that the dimensions of the secondary beam contained wf 200x200, the columns used the 400x400 profile and the main beam used the wf 400x200 and 350x350 profiles.